First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species - Gharali, Babak; Evenhuis, Neal (Zootaxa, 2017)
Two new species of Doliopteryx Hesse, D. nodahaki, sp. nov. and D. fratris, sp. nov. are described and illustrated. This marks the first record of the genus in Iran.